Internal erosion in dike‐on‐foundation modeled by a coupled hydromechanical approach. (18th December 2018) - Yang, Jie; Yin, Zhen‐Yu; Laouafa, Farid; Hicher, Pierre‐Yves
Summary: One of the major causes of instability in geotechnical structures such as dikes or earth dams is internal erosion, an insidious process that occurs over a long period of time. Research on this topic is still fairly new and much more needs to be understood in order to solve the problems posed by this phenomenon. This paper proposes a hydromechanical model based on porous continuous medium theory to assess how internal erosion impacts the safety of earthen structures. The saturated soil is considered as a mixture of four interacting constituents: soil skeleton, erodible fines, fluidized fine particles, and fluid. The detachment and transport of the fine particles are described by a mass exchange model between the solid and the fluid phases. An elastoplastic constitutive model for sand‐silt mixtures has been developed to monitor the effect of the evolution of both porosity and fines content induced by internal erosion upon the behavior of the soil skeleton. The model has been numerically solved with the finite element method. It has then been applied to the specific case study of a dike foundation subjected to internal erosion induced by the presence of a karstic cavity beneath the alluvium layer. The numerical results show the onset of erosion, the time‐space evolution of the eroded zone, and the hydromechanical response of the soil constituting the dike, all of which highlights the effects of the cavity location, the erosion rate, and the fines content.